Advocacy and archaeology : urban intersections - Britt, Kelly M.; George, Diane F. (New York : Berghahn Books, 2023)
"Archaeologists have a history of being prime agents of change, particularly in advocating for protection and preservation of historical resources. As more social issues intersect with archaeology and historical sites, we see archaeologists and others continuing to advocate for not only historic resources, but for the larger social justice issues that threaten the communities in which these resources reside. Inspired by the idea of revolution and excitement about the ways archaeology is being used in social justice arenas, this volume seeks to visualize archaeology as part of a movement by redefining what archaeology is and does for the greater good"--
List of illustrations -- Foreword / Margaret Purser -- Preface -- Acknowledgments -- Chapter 1 PANYC: the why, the then, and the now / Joan H. Geismar -- Chapter 2 "Cursed be he that moves my bones": the archaeologist's role in protecting burial sites in urban areas / Elizabeth D. Meade and Douglas Mooney -- Chapter 3 Digging truth: archaeology and public imagination in Shockoe Bottom / Ana Edwards and Matthew R. Laird -- Chapter 4 Seneca Village interpretations: bringing collaborative historical archaeology and heritage advocacy to the forefront and online / Meredith B. Linn, Nan A. Rothschild, and Diana diZerega Wall -- Chapter 5 Right to the city: community-based urban archaeology as abolitionist heritage / Kelly M. Britt -- Chapter 6 "Think like a historical archaeologist": moving beyond the primary source document in K-12 education / Elizabeth Martin -- Chapter 7 "DIVERS[]S" and the political legacies of an "experience-exhibition" / María Fernanda Ugalde and O. Hugo Benavides -- Chapter 8 American apotheosis: confronting exceptionalism in the (re)production of national identity / Diane F. George -- Afterword / Christopher N. Matthews -- Index.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 05, 2023).
JSTOR
Keywords: Urban archaeology; Archaeology -- Social aspects; Archaeology -- Political aspects; Social justice; Archaeology and history; Archéologie urbaine; Archéologie -- Aspect social; Archéologie -- Aspect politique; Justice sociale; Archéologie et histoire; historical archaeology; SOCIAL SCIENCE / Archaeology; Archaeology and history; Archaeology -- Political aspects; Archaeology -- Social aspects; Social justice; Urban archaeology; Electronic books